Effect of organic additives on in vitro seed germination of Borneo's endemic orchid, vanda dearei - Lee, Rui Xuan (Universiti Malaysia Sarawak (UNIMAS), 2015)
The effect of different organic additives on in vitro seed germination of Vanda dearei, an endemic species of orchid to Borneo was investigated. The seeds from about 6-month old seed pod of V. dearei was used as the plant material and allowed to grow on ½ MS medium supplemented with four different concentrations of banana homogenate (1 g/L, 2 g/L, 3 g/L and 4 g/L, w/v), coconut water (5%, 10%, 15% and 20%, v/v), potato homogenate (1 g/L, 2 g/L, 4 g/L and 6 g/L, w/v) and tomato homogenate (1 g/L, 2 g/L, 4 g/L and 6 g/L, w/v). The culture condition was maintained at a 16 light/8 dark photoperiod at room temperature of 25±2 . The seeds started to germinate after approximately one month of culture. The maximum germination percentage was recorded from ½ MS medium supplemented with 4 g/L (w/v) potato homogenate with 90.11±4.79% after 80 days of culture followed by 10% coconut water (v/v) (83.78±3.32%). The addition of organic additives has significantly enhanced the seed germination rate of V. dearei cultured in vitro. However, higher concentrations of coconut water at 15% and 20% (v/v) were found to be inhibitory for seed germination of V. dearei.